Enhancing the quality of lentil proteins via combination with whey proteins based on a dual process: a novel strategy through the incorporation of complexation and fermentation - Mohammad Alrosan (20089263) (2024)
In recent years, there has been a growing interest in developing a distinguished alternative to human consumption of animal-based proteins. The application of lentil proteins in the food industry is typically limited due to their poor solubility and digestibility. An innovative method of balancing lentil-whey protein (LP-WP) complexes with higher-quality protein properties was established to address this issue, which coupled a pH-shifting approach with fermentation treatment. The results showed that microorganisms in the water kefir influenced the quality of protein structures and enhanced the nutritional values, including increasing the total phenolic compounds and improving the flavor of fermented LP-WP complexes. The protein digestibility, pH values, microbial growth, total soluble solids, and total saponin and phenolic contents were hydrolyzed for 5 days at 25 °C. The FTIR spectrophotometer scans indicated significant (P < 0.05) changes to the secondary protein structure components (random coil and α-helix). This study showed that combining pH-shifting with fermentation treatment improves lentil and whey proteins’ structure, protein quality, and nutritional benefits. Other Information Published in: Food Science and Biotechnology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10068-024-01647-4